"Собори душ своїх бережіть, друзі. Собори душ!.." - Мех, Н. (Краєзнавство, 2018)
У статті зроблено спробу поглянути на роман Олеся Гончара «Собор» у широкому мовно-культурному вимірі. Розглянуто твір як духовний заповіт автора. Роман представлено очима сучасників. Особливу увагу приділено минулому українського народу, зокрема козаччині. Шана до славетних проявів українського духу на різних часових зрізах історичного розвитку нашого народу, рішучість у збереженні та плеканні духовних скарбів, любов до людей та Батьківщини – все це ми бачимо в «орлиному» «Соборі» Олеся Гончара. The article attempts to take a look at Oles Honchar's novel «SOBOR» in a broad linguisti cand cultural sense. The work is consideredas a spiritual testament of the author. The novelis represented by the eyes of contemporaries. Particularattention ispaidto the pastofour people, inparticular, the Cossacks. Musical accents in the composition, comparisons, epithets, and other artistic means testify that Oles Gonchar is a person of high spiritual culture and wide artistic preference. True music, architecture, history – all this is in the circle of artist's interests. All this is not ordinary and refers to true values, to cultural memory, to the golden fund of the people. The filigree work of the wizard, the attention to each word, and, at the same time, openness, courage in defending their views, their values and beliefs - all of this we find on the pages of the novel. Honoring the glorious manifestations of the Ukrainian spiritatvarioustimesections of the historical development of our people, the determinationt opreserve and cultivate spiritual treasures, love for people and the homeland – all this weseeinthe «eagle» «SOBOR» Oles Gonchar. This work reminds us of the «spirit of majestic freedom, directs us to eternity, to eternal values. It, like a gigantic bell, strives to awaken us, calls once more and once again to comprehend our lives, begs us «Save the soothsayers of you «SOBOR OF THE SOUL SAVE, FRIENDS ... SOBOR OF THE SOUL!..». В статье предпринята попытка взглянуть на роман Олеся Гончара «Собор» в широком культурном измерении. Рассмотрено произведение как духовное завещание автора. Роман представлен глазами современников. Особое внимание уделено прошлому украинского народа, в частности казачеству. Уважение к славным проявлениям украинского духа на разных временних срезах исторического развития нашого народа, решимость в сохранении и преумножении духовних сокровищ, любовь к людям и Родине – все это мы видим в «орлином» «Соборе» Олеся Гончара.